NILAI-NILAI PENDIDIKAN DALAM SURAH AL-SHAFF DAN RELEVANSINYA TERHADAP PENGUATAN PENDIDIKAN KARAKTER DI INDONESIA - Miswanto Miswanto; Muhammad Sohib (Makkah: Journal Of Islamic Studies, 2025)
This study aims to analyze the educational concepts and values ​​contained in Surah al-Saff and their relevance to the educational context in Indonesia. The study uses a qualitative approach with library research and thematic interpretation methods. Primary data are verses of Surah al-Saff and their interpretations in Tafsir Ibn Kathir, Tafsir al-Maraghi, and Tafsir al-Mishbah, while secondary data are obtained from Islamic education literature, character education, and national education policies. The results show that Surah al-Saff contains key educational values, namely integrity between words and deeds, collective discipline and order, commitment to truth, transcendental orientation, and the spirit of cooperation and sacrifice. These values ​​have strong relevance to educational challenges in Indonesia, particularly in strengthening character education and religious moderation. Surah al-Saff emphasizes the importance of role models, consistency of values, and synergy of all educational elements in shaping students who are faithful, have noble character, and are socially responsible. It is hoped that this research can provide a theoretical contribution to the development of Islamic education that is contextual and rooted in the values ​​of the Koran. This study also enriches the treasures of Al-Qur'an studies in the perspective of contemporary Indonesian national education.